Fermentation of Wheat Bran and Whey Permeate by Mono-Cultures of Lacticaseibacillus rhamnosus Strains and Co-culture With Yeast Enhances Bioactive Properties - Bertsch, Annalisse; Roy, Denis; LaPointe, Gisèle (Frontiers in Bioengineering and Biotechnology, 2020)
The aim of this work was to obtain a bioingredient (BI) with bioactive properties through the solid fermentation of a wheat bran-whey permeate (WB/WP) mixture with three strains of Lacticaseibacillus rhamnosus (R0011, ATCC 9595 and RW-9595M) in mono or co-culture with Saccharomyces cerevisiae. The choice of these strains was based on their capacity to produce the same exopolysaccharide (EPS), but at different yields. The solid fermentation of WB/WP revealed a similar growth pattern, sugar utilization and metabolite production between strains and types of culture. Lactic acid, soluble protein, free amino acid and phenolic compound content in BI were compared to NFWB. Water soluble polysaccharides (including EPS) were significantly increased in co-culture for (44%) ATCC 9595, (40%) R0011 and (27%) RW-9595M. The amount of bound Total Phenolic Content (TPC) as well as the antioxidant activity in BI were higher after fermentation. The free phenolic acid content was higher after fermentation with ATCC 9595 (53-59%), RW-9595M (45-46%) and R0011 (29-39%) compared to nonfermented NFWB. Fermentation by these strains increased the amounts of free caffeic acid and 4-hydroxybenzoic acid in both types of culture. The bound phenolic acid content was enhanced in co-culture for the BI obtained from the highest EPS producer strain RW-9595M which was 30% higher than NFWB. After in vitro digestion, bioaccessibility of free total phenolic acids was improved by more than 40% in BI compared to NFWB. The co-culture increased recovery of TPC (%) and antioxidant activity compared to monoculture for the strains in digested product. In contrast, the recovery of bound total phenolic acids in co-culture was 33% and 38% lower when compared to monoculture for R0011 and RW-9595M. Our findings provide new insights into the impact of LAB/yeast co-culture on the bioactive properties of fermented wheat bran.